The ingredients for spreading tourism culture: A field study of a sample of tourism establishments in the city of Sulaymaniyah (Raparin Journal of Humanities (RJH), 2024)
The importance of spreading tourism components lies in identifying these tourism structures and trying to use them. This is to raise the cultural level of the population towards tourism culture and raise the level of tourism culture in a way that treats tourists properly without distorting the culture of the host country. The aim of this study is to identify the factors for the Spreading the elements of tourism and defining society is crucial for building a tourism industry in developing nations, which is seen as a valuable economic resource. The research has two sides: theoretical and operational, and the descriptive analytical approach was applied. Theoretically, reference was made to numerous publications and academic theses that had been written specifically to the factors contributing to the rise of tourist culture. Regarding the operational element, a questionnaire was created and given to a random sample of guests in both these hotels and tourist areas. To gauge the questionnaire's stability, Cronbach's alpha was used. The study questionnaire was next examined for the presence of internal stability (credibility), which demonstrates the degree of coherence or correlation between the questionnaire's paragraphs. In order to determine whether the study's assumptions of which indicates that (there is an importance of the components in spreading the tourism culture) and another of which argues that (there is a statistically significant relationship between the components and the tourism culture). The research produced a number of recommendations and conclusions, the most significant of which was that the desire to promote tourism awareness and culture is one of the prerequisites for the development of tourism infrastructure because it is practically impossible to discuss the growth of the tourism industry without a high level of public awareness of the industry. The creation of a national center or institute for the dissemination of tourism culture, which develops educational programs and studies for the community, workers, and those involved in the tourism sector, is one of the most crucial recommendations. This will help everyone, especially the residents of Sulaymaniyah governorate, understand the significance of tourism culture.